 $\displaystyle y=\ \ln \left( {\frac{{{{e}^{{{{x}^{2}}}}}}}{{\cos (1-x)}}} \right)$

Before you Differentiate, simplify the expression

using the Laws of Logarithm $\displaystyle {{\log }_{a}}(\frac{x}{y})\ =\log {}_{a}x-{{\log }_{a}}y$ $\displaystyle y=\text{ln}\left( {{{e}^{{{{x}^{2}}}}}} \right)-\ln \left[ {\cos (1-x)\ } \right]$

and Laws of Logarithm again $\displaystyle {{\log }_{a}}{{x}^{c}}\ =c\log {}_{a}x$ $\displaystyle y={{x}^{2}}\text{ln}\left( e \right)-\ln \left[ {\cos (1-x)\ } \right]$ $\displaystyle y={{x}^{2}}-\ln \left[ {\cos (1-x)\ } \right]$

Differentiate the expression and simplify. $\displaystyle \frac{{dy}}{{dx}}=\frac{{{{x}^{3}}}}{3}-\frac{1}{{\cos (1-x)\ }}\times -\sin (1-x)\times -1$ $\displaystyle \frac{{dy}}{{dx}}=\frac{{{{x}^{3}}}}{3}-\frac{{\sin (1-x)}}{{\cos (1-x)\ }}$ $\displaystyle \frac{{dy}}{{dx}}=\frac{{{{x}^{3}}}}{3}-\tan (1-x)$

You can differentiate without first simplifying, but you will find that you will take more steps to get the answer. REMEMBER: The More (unnecessary) Steps = The More Mistakes.  See Post about Differentiation of ln with sine

New Elementary Math (E-Math) and Additional Math Group  Tuition Class near Admiralty MRT station.

A-Math & E-Math Tuition Class at Woodlands and Johor Bahru.